Over Accumulation or Investment Gap? - Kersten Kellermann; Carsten-Henning Schlag (Wirtschaftsdienst)
Abstract The fact that long-term interest rates are below the GDP growth rates in economies like Switzerland, Germany and the USA is often diagnosed as over-accumulation, which can be cured by an increase in debt-financed government consumption. However, this fiscal remedy assumes that the marginal net productivity of capital is equal to the interest rate. Evidence shows that this requirement does not apply. The marginal productivity of private and public capital has not been following the secular decline in the interest rate. This leaves room for an increase in debt-financed public investment. A prerequisite is that public decision-making with regard to investments and debt management are competently guided.